Microvascular Reconstruction of Composite Cranial Defects - BAYRAMİÇLİ, MEHMET NURİ ÜMİT (THIEME MEDICAL PUBL INC, 2010)
Microvascular reconstruction of composite cranium defects is challenging, and operative planning differs in various anatomic regions of the cranium. The aim of this article is to detail surgical strategies for microvascular reconstruction in different areas of the cranium. Fifty-eight free tissue transfers were performed in 54 patients with composite cranial defects between 1995 and 2009. The cranium was divided into six zones to classify the defects. Data on patient demographics, location and cause of the defects, technical details of surgical management, and complications were analyzed. Defects were secondary to ablative procedures in 45 patients. Eight patients had posttraumatic defects, and one patient had congenital defect. Nine different flap types were used in the series. Choice of recipient vessels and the use of interpositional vein grafts varied according to the site of the cranial defects. Microsurgical reconstruction of cranial defects can be performed safely with predictable outcome by methodic assessment of the problem and by careful attention to the details of the reconstructive plan. In this article, valid conclusions on the planning of microvascular reconstruction in different areas of the cranium have been determined.
Keywords: Reconstruction; free flap; cranium; composite defect; ANTERIOR CRANIOFACIAL RESECTION; ANTEROLATERAL THIGH FLAP; FREE TISSUE TRANSFER; SKULL BASE; SCALP DEFECTS; VEIN GRAFTS; HEAD; TUMORS; COMPLICATIONS; MANAGEMENT